PENGARUH INFRASTRUKTUR TERHADAP PEMBANGUNAN EKONOMI - Indirwan Indirwan; Muhammad Askari Zakariah; Nurhayati Nurhayati (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
The Kolaka Regent and the Kolaka Deputy Regent were present with the SMS Berjaya tagline (Strategi Mekongga Sejahtera Bekerja dan berkarya) which contained the Vision, Mission and 9 Priority Programs, where one of the points contained the acceleration of infrastructure development, the infrastructure development was carried out as an effort to encourage the district's economic development. Kolaka in general and Kolaka sub-district in particular in a better direction. The formulation of the problem in this study is whether Road and Drainage Infrastructure has an effect on economic development in Kolaka sub-district. The research method used includes the type of quantitative research, and uses the Cluster Area Random Sampling method as a sampling technique, as well as using questionnaires and interviews as data collection techniques and using Validity, Reality, Normality and Multiple Linear Regression Tests as questionnaire test tools and domain analysis as tools used in processing interview data. The results showed that road and drainage infrastructure had a positive but not significant effect on the economic development of the Kolaka sub-district. This can be seen if the length of the road increases by 1%, economic development only increases by 0.28%. Drainage infrastructure has a positive and significant influence on the economic development of the Kolaka sub-district. With a confidence level of 0.785.